Answer:
ab = 1
Step-by-step explanation:
A Reciprocal of a number is a number which when multiplied by the original number yields the multiplicative number, 1.
So the reciprocal of x would be x⁻¹ or ¹⁄ₓ
The information we are given states that the sum of the two non-zero numbers a and b equals the sum of their reciprocals.
So we can write this into an equation and solve,
(See image)
Once we solve, we get the equation (ab-1)(a+b) = 0
We are given info that a+b≠0
So for the above equation to be true, ab-1 has to equal 0
For <em>this</em> to be true, the product ab must equal 1
Answer:
a) 615
b) 715
c) 344
Step-by-step explanation:
According to the Question,
- Given that, A study conducted by the Center for Population Economics at the University of Chicago studied the birth weights of 732 babies born in New York. The mean weight was 3311 grams with a standard deviation of 860 grams
- Since the distribution is approximately bell-shaped, we can use the normal distribution and calculate the Z scores for each scenario.
Z = (x - mean)/standard deviation
Now,
For x = 4171, Z = (4171 - 3311)/860 = 1
- P(Z < 1) using Z table for areas for the standard normal distribution, you will get 0.8413.
Next, multiply that by the sample size of 732.
- Therefore 732(0.8413) = 615.8316, so approximately 615 will weigh less than 4171
- For part b, use the same method except x is now 1591.
Z = (1581 - 3311)/860 = -2
- P(Z > -2) , using the Z table is 1 - 0.0228 = 0.9772 . Now 732(0.9772) = 715.3104, so approximately 715 will weigh more than 1591.
- For part c, we now need to get two Z scores, one for 3311 and another for 5031.
Z1 = (3311 - 3311)/860 = 0
Z2 = (5031 - 3311)/860= 2
P(0 ≤ Z ≤ 2) = 0.9772 - 0.5000 = 0.4772
approximately 47% fall between 0 and 1 standard deviation, so take 0.47 times 732 ⇒ 732×0.47 = 344.
The value of x in terms of p is 15/p.
The value of x when p is -5 is -3.
Pls tell me if i’m wrong in any way!
Congruent because 2 is a larger number then one and 1 is a smalled number then 2
Answer:
188
Step-by-step explanation:
f(x)=4x² - 10+2
f(-7) = 4x² - 10 + 2
= 4(-7)² - 10 + 2
= 4 (49) - 10 + 2
= 196 - 10 + 2
= 188